Peningkatan Aktivitas Dan Kreativitas Belajar Matematika Siswa Melalui Model Pembelajaran Kontekstual - Nurdalilah; Reski Wahyuni Hasibuan; Puspa Riani Nasution (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2023)
This type of research is Classroom ActionResearch (CAR) by taking research subjects from Class X TKJ SMKS Al-Hasanah Sibuhuan. It consists of 20 students, 10 male students and 10 female students. The object taken in this study is to increase students' mathematics learning creativity in implementing classroom learning, which specializes in contextual learning strategies, as well as the teacher's role in classroom management. This Classroom Action Research (CAR) was carried out in two cycles which were equipped with Learning Implementation Plans (RPP), Teacher Handbooks (BPG), Student Worksheets (LKS), and test instruments including tests of students' critical thinking skills, student activity observation sheets, as well as teacher performance observation sheets managing learning. Before the instrument was used, it was tested first and obtained from the 10 tests tested there were 10 valid tests, 5 tests for cycle I and 5 tests for cycle II. The calculation shows that the test reliability coefficient is 0.84 for cycle I and 0.89 for cycle II and is stated learning creativity abilities in the first cycle obtained 65% of the minimum criteria sufficient, and for the second cycle 90%. The results of observations of student activity 79.58% of the criteria in the first cycle, increased to 88.33% in the second cycle. From the data analysis, it shows that the implementation of the actions taken has improved the teacher's ability to manage learning, from